Analisis E-Marketing Instagram Engagement pada Destinasi Wisata Kopeng Treetop Salatiga dan Guci Forest Tegal - Joseph Aldo Irawan; Lia Fitria Anugrah; Novi Khotimah; Ananta Budhi Danurdara; Haryadi Darmawan; Sukmadi Sukmadi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Tourism destination business management is starting to merge with technological developments. In an effort to adapt, the use of e-marketing in the tourism destination business is assisted by various digital platforms, one of which is Instagram. Instagram was chosen because it has many users in a wide range and the features it offers really help e-marketing activities in a business. The sample loci used in this research were Kopeng Treetop and Guci Forest. This locus was chosen because both of them have mutually satisfying similarities so that comparisons can be made. Using the mix method, researchers analyzed the data obtained from collecting data on likes, comments and the number of posts, then calculated it using a simple quantitative model and supported it by documentation, then analyzed it using triangulation to get in-depth thinking results. The research results found that there were similarities and differences in the use of Instagram e-marketing from the two loci, each of which has different abilities but also has the same opportunities in business. Through improvement efforts, in the future e-marketing development efforts can be carried out more optimally in order to achieve maximum visit levels.